以協同雲端技術為基礎分析財務交易決策支援系統 - 陳安斌; CHEN AN-PIN (My University, 2011)
在金融風暴過後民眾的財富大幅縮水，歐美經濟依舊是低迷不振，台灣的高所得與中低所得呈現越來越大貧富差距，企業對員工減薪、裁員，資產股票減少，間接使得人民實際所得差距日漸擴大。在外資及法人炒作的股票市場，不對稱資訊傳聞會造成民眾在做資產配置，會有錯誤的財務策略，造成不少資產的損失。本計畫用以行為方式之處理模式，從中分析動態價格及資金面流向，從中以大量資料中探勘出外資及法人進出資金交易，分析操作上的異動趨勢，提供投資人從中選擇出正確投資策略，降低資金上的錯誤配置，以逹均衡獲利。本計畫運用實際交易資料，應用協同技術之概念，對於動態價格環境進行理財策略規劃，並與舊有的模型互相比較投資損益之結果。因此，運用協同技術與雲端運算系統構建基本系統，以研究消費者投資行為流程，最適投資策略收益及隨時變動儲存績效資訊，進行有效率的投資策略，提供投資大眾能正確的資訊決策支援。

After financial crisis, people’s wealth has shrunk dramatically. Europe is still sluggish economy. Let the distance become bigger between rich and poor in Taiwan. Enterprises pay cuts, layoffs and asset stock decline makes people’s actual income indirectly. When getting asymmetric information between general investors and institutional investors, making the wrong strategy will cause the loss. Therefore, this purpose uses physical theory to analyze price and volume of Taiwan market, and extract the abnormal trend made by institutional investors from less information. When it’s asymmetric information, investors could detect the abnormal behavior early. The investors make less loss and stable profit with right strategy. In addition, this purpose use artificial intelligence methodology to adaptive the model for dynamic environment. According the environment of market the model provides the right strategy to investors, and reduces investors’ burden when planning. It wills empirical evidence in the Taiwan market, and measure the model of reliability and validity. Finally, the system built a prototype in the collaborative technology and cloud computing to research process as a service. Through collaborative cloud computing technology that utilization of computing and storage resources will be more efficient. The investors can be more flexible with different decision-making support services.
The Collaborative Cloud Based Financial Trading Decision Support System
Keywords: 協同技術; 行為財務學; 理財規劃; 雲端運算; Collaborative Technology; Financial Planning; Computational Intelligence; Cloud Computing.